Vaginoplastia com celulose oxidada: avaliação anatômica, funcional e histológica - Dornelas, Juliane Sá [UNIFESP] (2011)
Objective: To present and evaluate the histological, anatomical and functional results of the McIndoe procedure, as modified by the application of oxidized cellulose (SurgicelTM) in women with vaginal agenesis. Study design: Eleven patients with vaginal agenesis underwent vaginoplasty with or without uterovaginal cannulation using a mold that had been wrapped with oxidized cellulose. The surgeries were performed between January 2009 and January 2010. Eight of the patients had been diagnosed with Mayer-Rokitansky- Kuster-Hauser (MRKH) syndrome, and the remaining three had been diagnosed with cervicovaginal agenesis (CVA). The mean follow-up time was 14 months (range, 6-24 months), and it included clinical examinations and evaluation of the Female Sexual Function Index (FSFI). Neovaginal biopsies were taken from the patients with MRKH syndrome at the time of surgery and 1-12 months after surgery. Control tissues were taken from a group of patients without vaginal disease. The histology of the samples was evaluated to determine squamous epithelialization of the neovaginal tissue over time, and the total collagen content of the neovaginas were compared with normal control subjects. For statistical analysis we employed the ANOVA test and the t-test. Results: At 6 months, anatomical success was achieved in 100% of the MRKH syndrome patients (neovaginal length . 6 cm), and functional success was achieved in 100% of the patients who started their sexual life (FSFI score . 30). Biopsy results showed complete epithelialization of the neovagina after 5 monthsin all samples, and the amount of collagen content in the neovaginas progressively increased. After 6 months, the collagen content was comparable to that of a normal vagina. One major postoperative complication occurred in a patient with CVA, which culminated in death. The uterovaginal canalization procedure was unsuccessful at creating an outflow tract for regular menses in all cases. None of patients with CVA achieved anatomical or functional success. Conclusions: The procedure described here offers patients a functional vagina by means of a simple and low-cost procedure that elicits squamous epithelialization of the neovaginal vault, with total collagen content similar to that of normal vaginal tissue. It is a potential alternative therapeutic approach for MRKH syndrome but not applicable to cases of CVA.